TINJAUAN KASUS TERKONFIRMASI POSITIF COVID-19 TERHADAP IKLIM INVESTASI DI INDONESIA: PERAMALAN DAN KORELASI - Kadek Ari Pratiwi Kasuma; Yoga Dwi Nugroho (Seminar Nasional Official Statistics, 2020)
Indonesia’s economic growth is 5,02 percent in 2019. Initially, Indonesian economy predicted to grow better in 2020. However, in early 2020 COVID-19 virus emerged which caused a pandemic. The COVID-19 pandemic has an impact on social, economic, financial aspects, and investment climate. This study aims to predict the addition number of confirmed positive cases COVID-19 in Indonesia using the ARIMA model. This research also aims to identify the correlation between the addition number of confirmed positive cases COVID-19 and the daily closing price of Jakarta Stock Exchange Composite Index (JKSE). Data used in this study from March 2, 2020 to August 5, 2020. Based on the analysis, ARMA (1,1) ARCH (1) model is a suitable model for predicting COVID-19 data. The ARMA(1,1) ARCH (1) then used to predict the addition number of confirmed positive cases on 6 August 2020-10 August 2020. Based on the Pearson’s correlation analysis, the two variables have a correlation of 0,455. After the implementation new normal policy, economic activity in Indonesia began to grow again. In spite of the addition number of COVID-19 cases, various positive sentiments in the community such as discovery of the COVID-19 vaccine and various stimulus policies by the government led to a strengthening in Indonesia’s investment climate which affected the strengthening of JKSE price.